Anxiety level and functional dyspepsia incidence during COVID-19 pandemic - Zulfitri Zulfitri; Desi Maghfirah; Muhammad Ridho Akbar Eljatin; Sarah Firdausa; Zulfa Zahra (Intelektual Pustaka Media Utama, 2023)
The adaptation process of the learning system, the hospital environment, and the high risk of COVID-19 infection can be stressors for anxiety in clinical clerkship. Through the brain-gut–axis, the interaction of psychological factors, such as anxiety, can trigger symptoms related to functional dyspepsia. This study aimed to determine the relationship between anxiety levels and functional dyspepsia during the COVID-19 pandemic among clinical clerkship students. This research was conducted on clinical clerkship students/young doctors in 2021. This was an observational analytic study with a cross-sectional approach and involved 131 respondents. The hamilton anxiety rating scale (HARS) questionnaire was utilized to quantify the level of anxiety, while functional dyspepsia was measured based on Rome IV criteria. The data were analyzed by the Lambda (λ) coefficient of correlation test. This study revealed a significant relationship between anxiety level and functional dyspepsia during the COVID-19 pandemic.